MePAL6 regulates lignin accumulation to shape cassava resistance against two-spotted spider mite - Yao, Xiaowen; Liang, Xiao; Chen, Qing; Liu, Ying; Wu, Chunling; Wu, Mufeng; Shui, Jun; Qiao, Yang; Zhang, Yao; Geng, Yue (Frontiers in Plant Science, 2023)
The two-spotted spider mite (TSSM) is a devastating pest of cassava production in China. Lignin is considered as an important defensive barrier against pests and diseases, several genes participate in lignin biosynthesis, however, how these genes modulate lignin accumulation in cassava and shape TSSM-resistance is largely unknown. In this study, most genes involved in lignin biosynthesis were up-regulated when the mite-resistant cassava cultivars were infested by TSSM, noticeably, the MePAL gene presented the most vigorous induction. In addition, genome-wide characterization of MePAL gene family in cassava had identified 6 MePAL members, besides, the phylogenetic analysis, gene duplication, cis-elements and conserved motif prediction speculated that these genes may contribute to biotic stress responses in cassava. To further elucidate the potential correlation between PAL expression and TSSM-resistance, the most strongly induced gene MePAL6 were silenced using virus-induced gene silencing (VIGS) assay, we found that silencing of MePAL6 in TSSM-resistant cassava cultivar SC9 not only simultaneously suppressed the expression of other lignin biosynthesis genes, but also resulted in decrease of lignin biosynthesis, ultimately, leading to significant deterioration of TSSM-resistance. This study accurately identified MePAL6 as critical genes in conferring cassava resistance to TSSM, which could be considered as promising marker gene for evaluating cassava resistance to insect pest.